Control of Automated Guided Vehicles Without Collision by Quantum Annealer and Digital Devices - Ohzeki, Masayuki; Miki, Akira; Miyama, Masamichi J.; Terabe, Masayoshi (Frontiers in Computer Science, 2019)
Recent advance on quantum devices realizes an artificial quantum spin system known as the D-Wave 2000Q, which implements the Ising model with tunable transverse field. In this system, we perform a specific protocol of quantum annealing to attain the ground state, the minimizer of the energy. Therefore the device is often called the quantum annealer. However the resulting spin configurations are not always in the ground state. It can rather quickly generate many spin configurations following the Gibbs-Boltzmann distribution. In the present study, we formulate an Ising model to control a large number of automated guided vehicles in a factory without collision. We deal with an actual factory in Japan, in which vehicles run, and assess efficiency of our formulation. Compared to the conventional powerful techniques performed in digital computer, still the quantum annealer does not show outstanding advantage in the practical problem. Our study demonstrates a possibility of the quantum annealer to contribute solving industrial problems.